2020
DOI: 10.4103/1319-4534.322603
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of serous retinal detachment in preeclampsia

Abstract: A 24-year-old pregnant woman applied with 2 days of sudden vision loss. Funduscopy showed serous retinal detachment along in the right eye and tear was not found. In the left eye, there were two small subretinal fluid accumulationsThe patient was diagnosed with serous retinal detachment due to preeclampsia. Serous retinal detachment of the patient regressed spontaneously within 1 month. All pregnant women with gestational hypertension should undergo retinal examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…2 In most of the patients, SRD shows complete resolution within 2–12 weeks after delivery. 14 In our patient, the BP spontaneously decreased after birth, and the patient was discharged from the obstetrics and gynecology clinic with a prescription including methyldopa (Alfamet, Ibrahim Ethem, Turkey). In line with the literature, we observed that SRD gradually resolved, and visual acuity recovered completely.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…2 In most of the patients, SRD shows complete resolution within 2–12 weeks after delivery. 14 In our patient, the BP spontaneously decreased after birth, and the patient was discharged from the obstetrics and gynecology clinic with a prescription including methyldopa (Alfamet, Ibrahim Ethem, Turkey). In line with the literature, we observed that SRD gradually resolved, and visual acuity recovered completely.…”
Section: Discussionmentioning
confidence: 75%
“…In line with the literature, we observed that SRD gradually resolved, and visual acuity recovered completely. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%